Prophets, Priests and Preachers: Dene Shamans and Christian Missions in the Nineteenth Century - Abel, Kerry (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractThroughout the nineteenth century, European and Canadian observers recorded instances of “prophets” arising among the Dene in the northwest. These men and women reported having travelled to the land of the spirits or to heaven, where they learned new rules for human behaviour which would bring about a change of circumstances for the better. Missionaries of the Church Missionary Society and particularly the Oblates of Mary Immaculate were concerned about these events and interpreted them in a variety of ways. Anthropologists and historians have considered similar postcontact events in North American Indian societies as “revitalization movements” and “crisis cults.” These concepts are examined and found somewhat misleading when applied to the Dene prophets. Instead, the activities of these prophets are interpreted as manifestations of traditional cultural responses to the various pressures of life in a harsh northern environment.